2023
DOI: 10.1117/1.jrs.17.024515
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy evaluation of UAS photogrammetry and structure from motion in 3D modeling and volumetric calculations

Abstract: Photogrammetric surveying using unmanned aerial systems (UAS) and structure from motion (SfM) is a rapidly emerging technique that has been widely used as a valuable research tool in geodesy and related disciplines. We studied surveying and three-dimensional (3D) modeling based on UAS and SfM. In particular, we focus on the accuracy and quality of UAS-SfM in 3D modeling and volumetric calculation of a building with an overhanging feature. For this purpose, two aerial surveys were performed using a fixed-wing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…According to studies carried out in other works, remote sensing-based image capture (SfM) using remote sensing is reaching great popularity in the characterisation of landscapes with centimetre-level precision. For example, in landslide studies [43] (where it was shown that the use of multi-rotor UAVs improves the point cloud by 16% compared to the use of fixed-wing UAVs) or in the heritage preservation field [44] (in a study on a Monastery, the quality parameters of the point cloud were evaluated using what the author calls the Remotely Piloted Aircraft System (RPAS) and the TLS). However, in the field of archaeology, there are studies [45] that only approach this investigation using SfM without UAV.…”
Section: Comparison Between Sfmuav and Hmls Standardmentioning
confidence: 99%
“…According to studies carried out in other works, remote sensing-based image capture (SfM) using remote sensing is reaching great popularity in the characterisation of landscapes with centimetre-level precision. For example, in landslide studies [43] (where it was shown that the use of multi-rotor UAVs improves the point cloud by 16% compared to the use of fixed-wing UAVs) or in the heritage preservation field [44] (in a study on a Monastery, the quality parameters of the point cloud were evaluated using what the author calls the Remotely Piloted Aircraft System (RPAS) and the TLS). However, in the field of archaeology, there are studies [45] that only approach this investigation using SfM without UAV.…”
Section: Comparison Between Sfmuav and Hmls Standardmentioning
confidence: 99%